The atomic structure of bluetongue virus core - Grimes, J; Burroughs, J; Gouet, P; Diprose, J; Malby, R; Zientras, S; Mertens, P; Stuart, D; Stubbs, G (1999)
The structure of the core of bluetongue virus has been determined at 3.5 resolution, revealing molecular details of mismatched symmetry. This is the largest structure yet determined by X-ray crystallography.